Enhanced Electrochemical Performance of Graphite Anodes for Lithium-Ion Batteries by Dry Coating with Hydrophobic Fumed Silica - Lux, S. F.; Placke, Tobias; Engelhardt, C.; Nowak, Sascha; Bieker, P.; Wirth, Karl-Ernst; Passerini, Stefano; Winter, M.; Meyer, H-W (Journal of The Electrochemical Society, 2012)
Coating of electrode materials for lithium-ion batteries is usually performed in order to improve performance, safety and the processability of the raw material. Here, we apply a dry coating method of graphite with hydrophobic fumed silica particles. This method excludes the use of any harmful solvents and the nano-scale particles cover and stick to the graphite substrate by only adhesive forces. Furthermore, this dry coating method is easily mass-scalable and a high throughput can be obtained in a short processing time. The nanoparticle coating reduces the van-der-Waals forces between the graphite particles and leads in this way to better flowability of the graphite powder which is important for further processing and the production of electrode tapes. Furthermore, these core-shell particles were processed to composite negative graphite electrodes in combination with the water soluble binder sodium carboxy-methylcellulose. Electrodes obtained with the coated material displayed a smooth surface, a high mechanical stability and outperformed the unmodified ones in the electrochemical investigations.